Effect of irrigation methods and mulching on growth and yield parameters of chilli (Capsicum annum L.) in arid condition - R Kumhar, N Kumar, R L Bhardwaj, M M Sundria, S R (Journal of Spices and Aromatic Crops, 2018)
The research work was carried out to study the impact of various irrigation methods and mulching on plant growth, production and profitability of chilli cv. R.Ch. 1 at Agricultural Research Station, Mandor, Jodhpur during July, 2016 to February, 2017. The results of surface irrigation were compared with drip irrigation system under no mulch and in conjunction with plastic mulch. The results revealed that the crop was irrigated by drip irrigation on raise bed with 100 micron Linear Low Density Poly Ethylene plastic mulch (T8 treatment) exhibited significantly higher seedling survival at 15 and 30 days after transplanting (95.16% and 91.70%), highest plant height (47.10 cm at 45 DAT and 54.60 cm at harvest), highest number of branches (14.93) plant-1, maximum stem girth (2.32 cm) number of roots plant-1 (138.5), highest fruit set (38.47%), length of fresh fruit (12.56 cm), diameter of fruit (3.52 cm) and fresh weight of fruit-1 (8.42g) was observed. The maximum number of fruits plant-1(125), highest yield plant-1 (1052.5g), yield ha-1 (337.63q) and premier fruit quality score (9.11) with maximum net return (Rs.326407.28) and benefit: cost ratio (3.41) was also reported in same treatment. Comparatively minimum time (15 hours) required for one hectare irrigation was also reported in drip irrigation on raise bed with plastic mulch. This led to lower population of white fly plant-1 (4.53), minimum weed infestation (1.53 weed m-2), leaf curl (5.50%) and fruit rot (5.0%) incidence than other treatment combinations. The minimum growth, yield and profitability were reported in check basin method of irrigation without mulch (T1 treatment).